Habit formation, obesity, and cash rewards - Boris Augurzky; Thomas K. Bauer; Arndt R. Reichert; Christoph M. Schmidt; Harald Tauchmann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2018)
This paper examines weight loss and the formation of healthy habits through cash rewards in the context of a multi-phase randomized controlled trial involving 700 obese individuals. We find effects of monetary incentives for weight loss of up to EUR 300 on body weight during all experimental phases, including a period of a year and a half following the exposure to the financial rewards. We also find effects on healthy behavior during this follow-up phase. After the initial incentive period, we additionally provided participants who had lost a substantial amount of weight with monetary rewards of up to EUR 500. These had only short-term effects on body weight and healthy behavior. We argue that our findings are best explained by monetarily incentivized participants having formed healthy habits by the time the experiment ended and that only the speed of the transition to the new (health) equilibrium was affected by the additional rewards. Contrary to the pessimistic perspective presented in earlier empirical research on habit formation, our results suggest that a simple program relying on weight loss rewards can result in long-term health behavioral change.
Keywords: I12; I18; D03; C93; 330; field experiment; obesity; healthy behavior; habit formation; sustainability; monetary incentives